Impact of guideline-recommended versus non-guideline-recommended β-blocker and Doppler echocardiographic parameters on 1-year mortality in Thai ischemic cardiomyopathy patients: A prospective multicenter registry - Wongpraparut, Nattawut (BMC Cardiovasc Disord, 2020)
BACKGROUND: Ischemic cardiomyopathy is a high-cost, resource-intensive public health burden that is associated with a 1-year mortality rate of about 16% in western population. Different in patient ethnicity and pattern of practice may impact the clinical outcome. We aim to determine 1-year mortality and to identify factors that significantly predicts 1-year mortality of Thai patients with ischemic cardiomyopathy. METHODS: This prospective multicenter registry enrolled consecutive Thai patients that were diagnosed with ischemic cardiomyopathy at 9 institutions located across Thailand. Patients with left ventricular function < 40% and one of the following criteria were included: 1) presence of epicardial coronary stenoses > 75% in the left main or proximal left anterior descending artery or coronary angiography, and/or two major epicardial coronary stenoses; 2) prior myocardial infarction; 3) prior revascularization by coronary artery bypass graft or percutaneous coronary intervention; or, 4) magnetic resonance imaging pattern compatible with ischemic cardiomyopathy. Baseline clinical characteristics, coronary and echocardiographic data were recorded. The 1-year clinical outcome was pre-specified. RESULTS: Four hundred and nineteen patients were enrolled. Thirty-nine patients (9.9%) had died at 1 year, with 27 experiencing cardiovascular death, and 12 experiencing non-cardiovascular death. A comparison between patients who were alive and patients who were dead at 1 year revealed lower baseline left ventricular ejection fraction (LVEF) (26.7 ± 7.6% vs 30.2 ± 7.8%; p = 0.021), higher left ventricular end-diastolic volume (LVEDV) (185.8 ± 73.2 ml vs 155.6 ± 64.2 ml; p = 0.014), shorter mitral valve deceleration time (142.9 ± 57.5 ml vs 182.4 ± 85.7 ml; p = 0.041), and lower use of statins (94.7% vs 99.7%; p = 0.029) among deceased patients. Patients receiving guideline-recommended β-blockers had lower mortality than patients receiving non-guideline-recommended β-blockers (8.1% vs 18.2%; p = 0.05). CONCLUSIONS: The results of this study revealed a 9.9% 1-year mortality rate among Thai ischemic cardiomyopathy patients. Doppler echocardiographic parameters significantly associated with 1-year mortality were LVEF, LVEDV, mitral E velocity, and mitral valve deceleration time. The use of non-guideline-recommended β-blockers rather than guideline recommended β-blockers were associated with increased with 1-year mortality. Guidelines recommended β-blockers should be preferred. TRIAL REGISTRATION: Thai Clinical Trials Registry TCTR20190722002. Registered 22 July 2019. “Retrospectively registered”.